Axiological dimensions fixed in History textbooks exercises (Tempo e Argumento, 2021)
Assuming that the axiological dimensions are inexorably linked to other elements in the school history knowledge setting, and recognizing the exercises and activities of the textbook as a gap between assessment and learning, the purpose of this article is to identify how the axiological dimension of historical empathy has been fixed in this space for the legitimation of knowledge and learning. From a discursive approach that recognizes the political as the place of disputes for hegemonization in any social order, it was decided, methodologically, to prioritize the reference texts to address issues, statements, templates, and the articulation with the curricular contents, in the analysis. The proposal of this article is justified by the results obtained in a doctoral research in which it was found that, without prejudice to other important values, empathy in relation to historically excluded and marginalized groups constitutes the main axiological issue fixed in these exercises/activities.Keywords: Historical empathy; school history knowledge; textbook exercises; History textbook; history teaching.